Experimental Studies of Electron Affinity and Work Function from Aluminium on Oxidized Diamond (100) and (111) Surfaces. Issue 7 (5th May 2021) - James, Michael C.; Cattelan, Mattia; Fox, Neil A.; Silva, Rui F.; Silva, Ricardo M.; May, Paul W.
Abstract : Three different procedures are used to deposit aluminium onto O‐terminated (100) and (111) boron‐doped diamond, with the aim of producing a thermally stable surface with low work function and negative electron affinity. The methods are 1) deposition of a > 20 nm film of Al by high‐vacuum evaporation followed by HCl acid wash to remove excess metallic Al, 2) deposition of <3 Å of Al by atomic layer deposition, and 3) thin‐film deposition of Al by electron beam evaporation. The surface structure, work function, and electron affinity are investigated after annealing at temperatures of 300, 600, and 800 °C. Except for loss of excess O upon first heating, the Al + O surfaces remain stable up to 800 °C. The electron affinity values are generally between 0.0 and −1.0 eV, and the work function is generally 4.5 ± 0.5 eV, depending upon the deposition method, coverage, and annealing temperature. The values are in broad agreement with those predicted by computer simulations of Al + O (sub)monolayers on a diamond surface. Abstract : Three different vacuum procedures are used to deposit (sub)monolayers of aluminium onto O‐terminated diamond. For the various samples, X‐ray photoemission spectroscopy is used to determine the surface composition, whereas region‐selected ultraviolet photoelectron spectroscopy is used to measure the electron affinity and work function. These Al−O‐terminated diamond surfaces are discussed in relation to their potential use in thermionic emission devices.